LONG-TERM FOLLOW-UP OF SLIPPED CAPITAL FEMORAL EPIPHYSIS TREATED WITH IN SITU PINNING - Dr Rajeshkumar K Goyani; Dr Raj Krishna Goyal (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background Slipped Capital Femoral Epiphysis (SCFE) is a common hip disorder in adolescents, often requiring in situ pinning for stabilization. Long-term follow-up studies are essential to assess functional outcomes, complications, and disease progression. This study evaluates the clinical and radiological outcomes of patients with SCFE treated with in situ pinning over a 10-year period. Materials and Methods A retrospective cohort study was conducted on 100 patients (120 hips) diagnosed with SCFE and treated with in situ pinning between 2010 and 2015. Patients were followed for an average of 10 years. Functional outcomes were assessed using the Harris Hip Score (HHS), and radiographic evaluation included slip progression, femoroacetabular impingement, and osteoarthritis. Complication rates, including avascular necrosis (AVN) and chondrolysis, were recorded. Statistical analysis was performed using a paired t-test to compare preoperative and postoperative functional scores. Results At the final follow-up, the mean HHS improved from 55.2 ± 8.6 preoperatively to 89.5 ± 6.2 postoperatively (p < 0.001). Radiographic assessment showed that 15% of patients developed mild osteoarthritis, while 8% exhibited signs of femoroacetabular impingement. AVN was observed in 5% of cases, and chondrolysis occurred in 2%. Bilateral involvement was seen in 30% of patients. No significant differences were noted between stable and unstable SCFE groups in terms of functional outcomes. Conclusion In situ pinning remains an effective long-term treatment for SCFE, yielding favourable functional outcomes and a low complication rate. However, a subset of patients may develop osteoarthritis and femoroacetabular impingement over time, highlighting the need for prolonged follow-up. Further studies are required to optimize treatment strategies and prevent late-onset complications.